Reinventing Urban Planning and Building The Capacity For It - Nathaniel von Einsiedel (The Institute for Research and Community Services, Institut Teknologi Bandung, 1996)
Entering the 21st century, the world is undergoing a rapid change in many aspects of life. The emergence of a knowledge-based global economy has undermin ed old realities throughout the world, creating opportunities as well as problems. Without more effective urban planning, world cities will not be able to fully benefit from these opportunities. More effective urban planning, as an integral component of urban management, is essential to avoid the breakdown of world cities.This article is trying to present the fallacies and limitations of current urban planning practice against current and future conditions, and to provide a recipe for reinventing effec tive urban planning.